Pike-McConnell-Donaldson family papers - Conger, Edwin H. (Edwin Hurd), 1843-1907.; Donaldson, David K.; Donaldson, Lavinia Pike McConnell; McConnell, Edward F.; McConnell, James S.
Chiefly diaries and correspondence relating in part to the family's commercial interests in China from 1902 to 1909. Also includes account book, address book, appointment books, autograph book, calling cards, invitations, announcements, newspaper clippings, photographs, and scrapbooks. Persons represented include James S. McConnell and his daughter, Lavinia Pike McConnell Donaldson, David K. Donaldson, and family member and diplomat Edwin H. Conger. Other papers (1770-1967) relate to the settlement of the estate of Edward F. McConnell.
In part, microfilm edition only
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Donaldson family; McConnell family; Pike family; Diplomatic and consular service, American; China -- Commerce